ANALISIS EFISIENSI TRAFO FAKULTAS TEKNIK UDAYANA BUKIT JIMBARAN DENGAN PENGOPERASIAN FILTER AKTIF BERBASIS FLC - Adi Septiawan I N.Triya; I W.. Rinas; I.M. Suartika (Jurnal SPEKTRUM, 2021)
Disruption to the transfomator can result in losses that disrupt the flow of electricity toconsumers. Harmonics are disturbances that arise due to the operation of non-linearloads. The purpose of this study is to analyze the efficiency of the KA4214 transformerat the Udayana Bukit Jimbaran Engineering Faculty with harmonics, namely the R =16.9%, S = 13.8% and, T = 16.1%. . The method used is to simulate and analyze withthe results of harmonic measurements in existing conditions, active filters, and activefilters based on fuzzy logic controller using Matlab software. The optimal resultsobtained are using the fuzzy logic controller method with the results of R = 0.85% S =0.65% T = 0.39% and the efficiency results are 99.99%